Has persistence persisted in private equity? Evidence from buyout and venture capital funds - Harris, Robert S.; Jenkinson, Tim; Kaplan, Steven N.; Stucke, Ruediger (Journal of Corporate Finance, 2023)
This paper presents new evidence on performance persistence for U.S. private equity (buyout and venture capital) funds. We use high quality cash-flow data from Burgiss's large sample of institutional investors (as of December 2020) which allows us to examine how persistence has changed over more than three decades of fundraising. Venture capital (VC) performance remains remarkably persistent across funds raised by the same general partner (GP). In contrast, buyout funds' performance persistence becomes noticeably weaker over time. The patterns are different when we restrict the analysis to information that would have been available to investors – interim performance on the previous fund at the time a new fund is raised – rather than using final, or latest, performance. We find little evidence of persistence for buyouts, especially post-2000. We continue to find persistence for VC funds though it declines post-2000. The differences are driven by interim performance reported at the time of fundraising being only moderately correlated to final performance and GPs avoiding fundraising when interim performance is poor. Finally, we look at GPs who introduce new fund styles and find that performance is noticeably lower for buyouts (but not VC). Exploring the reasons for these divergent trends in persistence between buyout and VC is a promising area for future research.